Thinking with sound: exploring the experience of listening to an ultrasonic art installation - Robson,N; McPherson,A; Bryan-Kinns,N (ACM, 2024)
Entanglement theories are well established in HCI discourse. These involve a commitment to view human experience in encounters with technology as relational and contingent, and research apparatuses as co-producers rather than passive observers of phenomena. In this paper, we argue that sound is the sensory modality best suited to the investigation of entanglements. Materialist theoriesof sound and listening guide both the design of a novel interactive sound installation and the methodological approach of a participant study exploring the experience of listening. We present a diffractive analysis whereby micro-phenomenological interview data is read with sonic theories, generating accounts that might otherwise remain mute: the temporal fluctuation and physical feeling ofproximity in listener entanglements with sound, somatic intention setting, and plural interpretations of interactivity. Finally, we offer a series of provocations for HCI to embrace qualities of the sonic and consider epistemological positions grounded in other sense modalities.